PHYTOCENOTIC AND TYPOLOGICAL STRUCTURE OF VEGETATION IN THE CHODAKSOY BASIN (Modern American Journal of Biological and Environmental Sciences, 2025)
The study examines the phytocenotic and typological structure of vegetation in the Chodaksoy Basin, a southeastern segment of the Qurama mountain system in the northern Fergana Valley. The vegetation cover includes 53 associations, 13 formations, and 9 types. Xerophytic semi-shrublands and thermophilic juniper forests dominate a vast area (50176 ha), well adapted to the arid conditions of the basin. A detailed vegetation map (1:50,000 scale) of the Chodaksoy has been developed, identifying 653 species of vascular plants from 315 genera and 72 families. This work integrates historical botanical data and field studies to define the basin’s unique floristic structure and proposes management recommendations for overgrazing and ecological conservation.